Protective effects of ursodeoxycholic acid on ceftriaxone-induced hepatic injury in rats - Khaled A. Alhumaidha; Sally A. El-Awdan; Wafaa I. El-Iraky; Ezz- (Faculty of Pharmacy, Cairo University, 2014)
Ceftriaxone is a broad-spectrum semisynthetic cephalosporin antibiotic that causes partial damage in the liver manifested by transient elevation in some biochemical parameters. In this study, our aim was to investigate the use of ursodeoxycholic acid (UDCA) in prevention of the hepatotoxic effect and biochemical changes induced by ceftriaxone in rats. Rats were divided into six groups (control, UDCA 20 mg/kg, ceftriaxone 180 mg/kg, UDCA + ceftriaxone 180 mg/kg, ceftriaxone 360 mg/kg, and UDCA + ceftriaxone 360 mg/kg). Ceftriaxone was injected intraperitoneally, and UDCA was given orally daily for four consecutive weeks. Then liver functions (serums AST, ALT, ALP, direct bilirubin, and total protein) were assessed. Histopathological examination was performed. Treatment of animals with ceftriaxone caused elevated activities of serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) as well as total bilirubin level. These elevations in liver enzymes were decreased by combination ceftriaxone with UDCA. In addition, ceftriaxone caused a significant increase in malondialdehyde (MDA) and nitric oxide (NO) content but significant decrease in glutathione (GSH) content. Combination of UDCA and ceftriaxone resulted in a significant decrease in MDA, NO content and significantly elevated GSH content. It could be concluded that UDCA acts as an effective hepatoprotective agent against liver dysfunction caused by ceftriaxone, and this effect might be related to its antioxidant properties. Hepatic functions should be monitored, and the dose should be adjusted during ceftriaxone therapy.